Pra Perancangan Pabrik Glucitol Dari Tepung Tapioka Dengan Proses Hidrogenasi Katalitik - Purwaningsih, Dian Yanuarita (Institut Teknologi Adhi Tama Surabaya, 2024)
Glucitol is the result of glucose reduction by changing the aldehyde group to a hydroxyl group, hence the name sugar alcohol. Sugar substitute sweeteners have various requirements, namely having a sweet taste, not causing toxicity to the body, calorie, and can be produced in large capacities. The most relevant sugar substitute with these criteria is glucitol. Glucitol factory is planned to be established in Jombang Regency, East Java with a production capacity of 20,000 tons/year. The raw material used in this glucitol factory is using tapioca starch raw material with a catalytic hydrogenation process. In the manufacture of glucitol there are 2 important processes, namely, the first process converts strach into glucose or dextrose with supporting raw materials for amylase enzymes and glucoamylase enzymes in the main tool, namely the reactor. In the catalytic hydrogenation process glucose or dextrose is reacted with hydrogen gas at high temperature and pressure with the help of the addition of nickel raney catalyst. The resulting glucitol is then purified in the evaporator to produce 70% glucitol. In the design of the Glucitol factory requires a total capital investment of Rp. 197,294,444,028 The total production cost of this factory is Rp. 552,393,444,402 with annual sales of Rp. 800,000,000,000. From the economic analysis, BEP was obtained at 23.7% with POT for 2.122 years and IRR of 64.14%. In terms of engineering and economics, this plant is feasible to establish